Comparison of professional and on-farm trimming methods in dairy cattle herds exposed to traumas - Gudaj, Richard; Brydl, Endre; Komlósi, István (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2011)
Lameness is third the most expensive diseases after mastitis and reproductive disorders. When remodelling dairy operations and introduction of novel technologies many farmers are still being tempted to save production costs in making hoof trimming either by themselves or giving that task to employees. In this study, further challenges such as changes in feed rations, heat stress, prolonged rainfall and/or other management practices effect of hoof trimming methods were recorded in 17 Hungarian dairy farms in 2010 and 2011 in a period lasting from May until November. Where building works were carried and trimming was done by trimmers being farm workers there was in average 22.8% increase in clinical lameness in comparison to average increase of 2.1% where professional trimmers where employed. Another type of farms was where mycotoxins were present in silage and where extreme level of urea in milk was reported. In those cases when on-farm trimmers worked 17.6% increase in lameness was monitored in contrast to 15.2% increase when professional trimmers were treating cows. Finally, when there was a swap from on-farm trimmers to professional trimmers 13.6% fewer cows were found with clinical lameness. Where professional trimmers where changed for on-farm trimmers 21.6% increase in occurrence of lameness was measured. In conclusion, traumas affecting the herd can be effectively minimised by providing professional trimming in comparison to on-farm trimming (increase of 1.9% vs. 15.3% respectively, ± S.E.M. 3.84, p < 0.05).